Development of Student Worksheet Based on Discovery Learning to Improve Student’s Concept Understanding - D. Anggraini; S. Susilowati (Universitas Negeri Yogyakarta, 2022)
This research aimed to (1) produce student worksheet based on discovery learning to improve students’ conceptual understanding, (2) analyze the practicality of student worksheet based on students’ responses, and (3) test the effectiveness of student worksheet to improve students’ conceptual understanding. The research used research and development (R and D) method with a 4D model. The trial design used a one-group pretest-posttest. The instruments were the eligibility validation sheet of student worksheets, student response questionnaires, observation sheets, and instrument tests. The data analysis techniques were a five-scale score conversion, implementation of the lesson plan, the percentage of the practicality of the student worksheet, Wilcoxon signed rank test, and n-Gain. The result showed that (1) student worksheet based on discovery learning was feasible to use with the result of the assessment from material and media experts in the very good category, (2) the practicality of the student worksheet was practical with a practicality percentage of 64% in a practical category, and (3) the student worksheet was effective to improve students’ conceptual understanding as seen by the result of the Wilcoxon signed rank test asymp. Sig (2-tailed) 0.001 less than 0.025. So, there were differences in understanding concepts before and after using the student worksheets. The result was strengthened by the n-Gain analysis of 0.4 with a medium category, and there is a significant increase in conceptual understanding.